2021
DOI: 10.1016/j.apmr.2021.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With COVID-19 Benefit from Rehabilitation? Functional Outcomes of the First 100 Patients in a COVID-19 Rehabilitation Unit

Abstract: Objective To determine the benefits associated with brief inpatient rehabilitation for Covid-19 patients. Design Retrospective chart review. Setting A newly created specialized rehabilitation unit in a tertiary care medical center Participants Consecutive sample of the first 100 patients with Covid-19 infection admitted to rehabilitation. Intervention Inpatient rehabilitation for post-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
166
3
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(194 citation statements)
references
References 34 publications
10
166
3
15
Order By: Relevance
“…A recent study conducted in 100 COVID-19 patients (mean age of 66 years) evaluated the inpatient rehabilitation for post-acute care and reported that grip strength was positively/moderately correlated with Barthel index (assessing overall strength and physical functioning), and negatively/moderately correlated with the duration of intensive care unit stay. 19 Another study recruiting 150 hospitalized COVID-19 patients (mean age of 53 years) compared the musculoskeletal findings (including grip strength) and revealed that female (but not male) patients with severe COVID-19 disease had lower grip strength as compared to nonsevere ones. 20 In our relatively larger study (N=312) with younger subjects (mean age of 46 years), we found that low grip strength independently increased (about three times) the risk of severe disease course in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in 100 COVID-19 patients (mean age of 66 years) evaluated the inpatient rehabilitation for post-acute care and reported that grip strength was positively/moderately correlated with Barthel index (assessing overall strength and physical functioning), and negatively/moderately correlated with the duration of intensive care unit stay. 19 Another study recruiting 150 hospitalized COVID-19 patients (mean age of 53 years) compared the musculoskeletal findings (including grip strength) and revealed that female (but not male) patients with severe COVID-19 disease had lower grip strength as compared to nonsevere ones. 20 In our relatively larger study (N=312) with younger subjects (mean age of 46 years), we found that low grip strength independently increased (about three times) the risk of severe disease course in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Hermann et al first reported that current pulmonary rehabilitation (PR) developed for pneumonia patients can improve physical performance in the six-min walk test (6MWT) of critical COVID-19 patients taken from a Swiss cohort of 28 patients who have been admitted to the ICU between March and May 2020 [8]. Subsequent studies on post COVID-19 patients reported on more variable PR outcomes probably because many of these studies focused on patients' characteristics after acute illness [3,9], used different outcome assessments (e.g., 6MWT vs. sit-to-stand test, Functional Independence Measure (FIM) vs. Barthel Index) [10][11][12][13][14], different PR settings (e.g., immediately post-ICU [12] vs. discharged from acute hospitalization [10,14]), and had a lack of control groups. In addition, the assessment of the minimal clinically important difference (MCID) is missing in most of previous studies, making it difficult to estimate the relevance of clinical improvement [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible to recommend moderate-intensity exercise activities to patients with COVID-19. However, it has been reported that one of the most effective intensities for increasing endorphins and reducing stress during exercise is moderate intensity, as regular exercise training can modulate some stress hormones and immunity [12]. Moderate exercise increases stress hormones, such as cortisol levels, which can suppress the immune function in a short time [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Piquet et al (2021) on rehabilitation time in patients with COVID-19, the researchers included two sessions of exercise in their rehabilitation program (with a researcher-made protocol). The first exercise program was intended to strengthen the overall movement related to body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation